Answer: g(x) = f(x) + 9
==========================================================
Step-by-step explanation:
Replace f(x) with y. This is valid because both represent outputs of a function. This means f(x) + 9 is the same as y+9, which means "move every point up 9 units".
For instance, the point (1,1) turns into (1,10) after moving it up 9 units. Here we added 9 to the y coordinate while keeping the x coordinate the same. You can write the translation rule as
![(x,y) \to (x, y+9)](https://img.qammunity.org/2021/formulas/mathematics/high-school/tv9eztl43t5uhn0mcv3ibwynj12zje72i6.png)